Biopolymers Online 2001
DOI: 10.1002/3527600035.bpol1010
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Humic Substances

Abstract: Introduction and Historical Outline Occurrence Hydrophobic and Hydrophilic Fractions Chemical Structure Elemental Composition Molecular Size Distribution and Charge Spectral Absorbance and Fluorescence Infrared Spectra Mass Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 61 publications
2
24
0
2
Order By: Relevance
“…On the other hand, together with decaying of primary producers, humic matter might contribute to the sediment organic carbon content, as a function of transportation through the coastal wave erosion at Sinop peninsula and autochtonously derived matter from biological activities. Because, C/N ratio is reported 76 for FA and 50 for HA in soil seepage (Frimmel, 2001) and HA with high C/N ratios (71.48-87.36) have been detected in the river bottom sediments by Rahman et al (2010). There was no significant difference between TOC values in Sinop and İğneada sediments but higher C/N ratio in the Sinop sediment ( Figure 5) could be attributed to preferential nitrogen depletion in N-rich labile compounds (like proteins) during early diagenesis of OM (Krishna et al, 2013).…”
Section: Toc In the Middle Coasts Of The Black Sea (Between Bartın Anmentioning
confidence: 95%
See 3 more Smart Citations
“…On the other hand, together with decaying of primary producers, humic matter might contribute to the sediment organic carbon content, as a function of transportation through the coastal wave erosion at Sinop peninsula and autochtonously derived matter from biological activities. Because, C/N ratio is reported 76 for FA and 50 for HA in soil seepage (Frimmel, 2001) and HA with high C/N ratios (71.48-87.36) have been detected in the river bottom sediments by Rahman et al (2010). There was no significant difference between TOC values in Sinop and İğneada sediments but higher C/N ratio in the Sinop sediment ( Figure 5) could be attributed to preferential nitrogen depletion in N-rich labile compounds (like proteins) during early diagenesis of OM (Krishna et al, 2013).…”
Section: Toc In the Middle Coasts Of The Black Sea (Between Bartın Anmentioning
confidence: 95%
“…C/N ratios were not very different but higher C/N ratio in Bartın surface sediment also indicated nitrogen depletion. High C/N ratios in Bartın, Bafra, Samsun and SB1 could be due to terrestrial sources which have been observed with C/N ratios: 17.5-12.1 (Prahl et al, 1994) and could be due to the contribution of the wastewaters (untreated municipal and industrial) which may also contain humic matter (with C/N:17;Frimmel, 2001). High organic matter has been reported (Bakan and Arıman, 2004) and TOC value was similar with this study around the same location in the Samsun Bay.…”
Section: Toc In the Middle Coasts Of The Black Sea (Between Bartın Anmentioning
confidence: 97%
See 2 more Smart Citations
“…The ratio of spectroscopic absorptivities at wavelengths of 465 and 665 nm for DOM (E 4 /E 6 ratio) were employed for the general molecular composition, chemical structure, and diagenetic characteristics of DOM (Aiken et al 1985;Chen et al 1977). Specific ultra-violet absorbance (SUVA) values measured at wavelengths at 254 and 280 nm were also used for the aromatic property of DOM (Aiken et al 1985;Frimmel 2001). Relative size and weight of DOM were estimated using highpressure size exclusion chromatography (HPSEC) as described in a prior study (Zhou et al 2000).…”
Section: Dissolved Organic Matter Characterizationmentioning
confidence: 99%